2015
DOI: 10.1111/iju.12717
|View full text |Cite
|
Sign up to set email alerts
|

Oncological outcome after radical prostatectomy: Marital status does not make a difference

Abstract: Objectives: To examine the impact of marital status on prostate cancer characteristics at radical prostatectomy and oncological outcome after surgery at a high-volume center. Methods: We relied on the Martini-Clinic Prostate Cancer database and investigated 8088 prostate cancer patients treated with radical prostatectomy between January 2000 and March 2011. We analyzed differences in clinical and pathological characteristics according to marital status (married and partnership vs single). Additionally, we reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Marital status, as a pivotal social exterior factor for cancer patents, has been investigated the associations with outcomes of prostate cancer patients previously (2729). Although marital status does not affect biochemical recurrence-free and metastases-free survival after radical prostatectomy (28), it is reported to be an independent predictor of OS and CSS in men with prostate cancer, which is consistent with our study (27, 29).…”
Section: Discussionsupporting
confidence: 91%
“…Marital status, as a pivotal social exterior factor for cancer patents, has been investigated the associations with outcomes of prostate cancer patients previously (2729). Although marital status does not affect biochemical recurrence-free and metastases-free survival after radical prostatectomy (28), it is reported to be an independent predictor of OS and CSS in men with prostate cancer, which is consistent with our study (27, 29).…”
Section: Discussionsupporting
confidence: 91%
“…The effect of marital status on the survival of patients with PCa who have undergone RP has been studied using SEER and the Martini-Clinic Prostate Cancer database ( 8 , 11 ). However, the results of these investigations have not been consistent and no studies have been conducted focusing on the heterogeneity of unmarried patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study ( 10 ) consisting of 3,570 patients with PCa treated in three prospective Radiation Therapy Oncology Group clinical trials revealed that the survival rates of unmarried individuals were significantly decreased compared with married individuals. However, a study by Schiffmann et al ( 11 ) using the Martini-Klinik Prostate Cancer database indicated that married men with PCa did not have a significantly higher OS rate compared with SDW men over follow-up period of 48 months.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations